Examining Mental Health Differences Among Transfer University Students Seeking Counseling Services. Issue 4 (1st October 2016) - Daltry, Rachel; Mehr, Kristin E.
ABSTRACT: This brief report was designed as a follow-up to a study that found that compared to nontransfer students that presented to the counseling center, transfer students who presented to the counseling center endorsed higher levels of symptoms of depression and social anxiety, as well as more academic and family problems. The current study investigated mental health differences within the transfer student population based on when (i.e., this semester; last semester; last year; 2 years ago; more than 2 years ago) and from where (i.e., community college vs. 4-year institution) students transferred. There were no significant differences based on when and from where students transferred. However, these findings still may be clinically meaningful and implications are presented.